Corporate image influence on the satisfaction with the quality of services of consumers: a case study of mobile companies - Kavaliauskaitė, Ieva (Information & Media, 2017)
Various investigations have been carried out in connection with customer behavior for marketing; the number of such studies is constantly growing. Obviously, customer behavior is an important area of research for corporate companies. Yet the recent years have revealed a tendency of developing corporate image by positioning means of communication. So far, the subject is little studied, as a company may aim to create a corporate relative attractiveness to the consumer through a variety of communication channels. Therefore, it is important to find out what impact does the corporate image of the user have on the attraction and retention of clients in the current market conditions. The main question posed in this article is how corporate image can help to build customer loyalty. According to this problem, there is an object – the corporate image and service quality ratio. The main purpose of this article is to estimate how important is the corporate image for the customer’s satisfaction with the quality of service. The theoretical analysis is based on scientific literature. The author forms the model of the customer’s needs. The main elements of the model are corporate image and service/product quality. These elements include criteria. In this study, the author tries to understand what are the main criteria that lead the customer’s choice and loyalty. For this reason, two research methods were applied – qualitative and quantitative. Lithuanian mobile companies were selected as the study objects of this research. The exploratory study helps to find out the main customer needs regarding mobile services. Also, a connection is found between practice and theoretical model. Quantitative research was used in order to check the hypothesis. The results of the research approved two hypotheses: H1 – corporate image has an impact on a user’s perception of service quality and a user’s satisfaction; H2 – corporate image and customer satisfaction are the main keys in gaining customer loyalty. The results show that there is a link between corporate image and service quality perceptions – the better the company’s image that a user has in his mind, the more the user is satisfied with the services provided by the company in question. Other aspects during the study were as follows: 1) corporate image has greater importance to the customer’s choice; 2) the quality of service has greater importance to the customer’s loyalty. In order to attract consumers, corporate image communication is the appropriate instrument used to manipulate the perception of a company in the consumer’s mind. The main corporate image manipulation object should be value for money, because so far there is no marketing, advertising or public relations measures that would affect customers more than the cost of services.